Effect of Azotobacter and Nitrogen Levels on Fruit Yield and Quality of Bell Pepper - Bhattarai, Dhruba R; Poudyal, Krishna P; Pokhrel, Shanta (Nepal Journal of Science and Technology, 2012)
Inorganic fertilizers alone cannot sustain high levels of productivity. It may cause deterioration of soil environment leading to low productivity. An investigation was carried out to develop integrated nutrient management technology for fruit yield of bell pepper (Capsicum annuum L.). The experiment was conducted at Horticulture Research Division, Nepal Agricultural Research Council Khumaltar, Lalitpur during 2010/011. The experiment was laid out in a randomized block design with three replications and having seven treatments viz., Control (100% NPK), Azotobacter + 25% N + PK, Azotobacter + 50% N + PK, Azotobacter + 75% N + PK, Azotobacter + FYM + 25% N + PK, Azotobacter + FYM + 50% N + PK, Azotobacter + FYM + 75% N + PK. Among the tested treatments, T7 (Azotobacter + FYM + 75 % N + PK) recorded the maximum plant height (66.18 cm), number of primary branches (8.20) and fruit yield (18.08 kg) per plot. DOI: http://dx.doi.org/10.3126/njst.v12i0.6475 Nepal Journal of Science and Technology 12 (2011) 29-34